Evaluation of the high-rate GNSS-PPP method for vertical structural motion - Kaloop, M.; Yigit, Cemal Ozer; Dindar, A.; Elsharawy, M.; Hu, J. (Maney Publishing, 2018)
© 2018, © 2018 Survey Review Ltd. This study aims at the investigation of GNSS-PP method to determine the dynamic characteristics of structures. Cantilever steel bars having lengths of 70, 100 and 120 cm were tested under dynamic excitation. The GNSS was used to measure the natural frequencies and damping values of all the tested cantilever structures. The GNSS data were processed using relative GNSS positioning and PPP methods. The results obtained using these two methods were also compared with the dynamic characteristics obtained by applying the theoretical and finite element (FE) methods. Furthermore, it is investigated the impact of the stable data length before oscillation events on kinematic PPP. The study showed that the maximum difference among the experimental results in terms of natural frequencies proceeded using PPP is 0.08 Hz when compared with the theoretical and FE results. Furthermore, there is no difference between the PPP and relative GNSS positioning in determining the dynamic behaviour of structures eventhough roving GNSS antenna remains motionless for short-time, such as a few-minutes, before an event occurred.